Multimodality in EAP Objectives and Practice - Hatice Sezgin (Literacy Trek, 2023)
Academic discourse is complex and dense regarding the information it conveys by nature. This complexity requires more effective ways of communication, which is possible by utilizing different modes of meaning-in other words, multimodality. English for Academic Purposes (EAP) aims to prepare learners for the academic discourse that they will be exposed to during their studies. Accordingly, multimodality has become one of the skills learners require to develop during their EAP experiences. This study attempts to reveal how much multimodality is included in EAP objectives and practices. For that purpose, target skills defined for academic English by the Global Scale of English (GSE) (Pearson, 2019) are analyzed to study the multimodal aspect of objectives. For the practice aspect, the tasks in two EAP course books are analyzed using a qualitative approach. The results of the analyses revealed that the use of multiple modes is set as an objective skill for EAP learners within the descriptors of GSE, especially for academic speaking, and this expectation is reflected within the tasks designed in EAP coursebooks. These findings are in agreement with the assumption that multimodality is considered a necessity for academic contexts and, therefore, EAP.